(untitled) (Fiep Bulletin - online, 2015)
The aim of this study was to characterize the thematic and theoretical-methodological trends in the publications on handball, spread by dissertations and theses submitted in Brazilian stricto sensu graduate programs. A documental analysis of eighteen studies carried out between 1990 and 2002 was done. The documental analysis was performed based on the Analytical Matrix of Academic Production on Physical Education (RESENDE et al, 2004). The results have revealed a low number of researches on handball that resulted from a mature academic production.